Implementation of a Disease Management Program in Adult Patients With Heart Failure. Issue 6 (November 2020) - Charais, Chantel; Bowers, Margaret; Do, Olamide Oladipo; Smallheer, Benjamin
Abstract : Background: Approximately 5.7 million people in the United States are diagnosed and living with heart failure (HF), with projected prevalence rates to increase 46% by 2030. Heart failure leads hospital admissions in the United States for individuals 65 years or older, with many acute exacerbation admissions resulting from a lack of medication management, poor patient treatment plan adherence, and lack of appropriate follow-up within the health care system. In 2017, the 30-day HF readmission rate at the facility of implementation was 27%, 3% higher than the national average and, more specifically, 18.5% for the cardiac care unit (CCU). Objective: The aim of this study was to develop an HF disease management program to reduce 30-day readmission rates for HF patients through the implementation of a structured program including self-care education utilizing the teach-back method, multimodal medication reconciliation, multidisciplinary consultation, telephone follow-up within 48–72 hr of discharge, and follow-up visit within 7–10 days of discharge. Primary Practice Setting: The implementation of the disease management program took place at a major military treatment facility in the continental United States. The facility is a teaching facility housing a 272-bed multispecialty hospital and an ambulatory complex. The implementation took place on the CCU, the primary unit for cardiac admissions, with approximately 30 admissions a month for a primary diagnosis of HF. Methodology and Sample: In August 2018, a multidisciplinary disease management program was implemented to include patient education utilizing the teach-back method, multimodal medication reconciliation, multidisciplinary consultation, telephone follow-up within 48–72 hr of discharge, and follow-up visit within 7–10 days of discharge. Data were collected and analyzed for 90 days and compared with retrospective data from 2017. Findings: Participants in the disease management program had a statistically significant improvement ( p < .001) in the hospital readmission rate. The overall 30-day readmission rate decreased from 27% to 10.2% during the implementation period, a decrease of 38%. Ninety-three percent of the patients completed the self-care education, and telephone follow-up was successfully achieved with 96% of these patients. Only 4 patients in the HF disease management program experienced readmission within 30 days. Patients and caregivers reported increased satisfaction with their care due to the disease management program and increased follow-up with care. Implications for Case Management Practice: The findings of this innovation suggest that a multidisciplinary disease management program can reduce avoidable 30-day readmissions. The program improved patient follow-up and decreased follow-up appointment no-shows. Multiple participants expressed increased patient satisfaction. The program supports the need for coordinated, interdisciplinary disease management to improve the quality of life of those affected by HF and improve the use of resources to reduce the overall health care burden. Case management is critical to the organized care of HF patients due to the complex, individualized care to achieve optimum patient outcomes.